Quantifying leaf herbivory: A guide to methodological trade‐offs and best practices - Tatiana Cornelissen; Gisele M. Mendes; Fernando A. O. Silveira; Wesley Dáttilo; Roger Guevara; Ramiro Aguilar; Maria Gabriela Boaventura; Ricardo Campos; Ek del Val; Guilherme Ramos Demetrio; Marcilio Fagundes; Rafael de Paiva Farias; et al. (Ecology, 2026)
Leaf herbivory is a ubiquitous ecological interaction that varies significantly in intensity across species, habitats, and biogeographic regions. Although quantification of leaf damage is crucial for understanding many ecological processes, the accuracy and precision of various damage estimation methods used by researchers, including visual estimation, digital image analysis, and artificial intelligence, have not been evaluated and compared. We use a phylogenetically diverse group of tropical plants to compare the accuracy and precision of damage estimation methods and use the results to provide a guide to herbivory estimation that balances the advantages and disadvantages of each method. We found that visual estimation tended to overestimate herbivory levels compared to digital methods but was 15 times faster and improved in accuracy and speed with training. Conversely, deep‐learning algorithms underestimated herbivory relative to image analysis with ImageJ when it was on the margin, but showed similar accuracy for damage inside of leaf margins. Our results indicate that while visual methods allow for rapid assessment of large sample sizes and are suitable for detecting broad patterns of damage, image analysis is crucial for accurate and precise quantification. The disadvantages of each method, however, can be minimized through proper training and efficient use of each tool, and we therefore provide a guide of practical approaches to herbivory estimation.

Enhancing river flow predictions in MOHID-Land through integration of gridded soil data and hydraulic parameters using the MOHID SOIL TOOL - Dhiego da Silva Sales; David de Andrade Costa; Jader Lugon Junior; Ramiro Joaquim de Jesus Neves; Antonio José da Silva Neto (Environmental Modelling & Software, 2026)

Evaluating the role of fire over a decade in a tropical mountainous forest-grassland mosaic - Juliana Kuchenbecker; Yumi Oki; Flávio Camarota; Frederico S. Neves; Diego R. Macedo; Bárbara Silva Ferreira; Ramiro Aguilar; Lorena Ashworth; Ezequiel Fabiano; Bárbara Dias Araújo; Amanda Ponce De Leon; Bruna Ribeiro Silva; et al. (Journal of Mountain Science, 2024)

Evaluation of precipitation products in a Brazilian watershed: Tocantins-Araguaia watershed case study - Débora R. Pereira; Ana R. Oliveira; Maurício S. Costa; Tiago B. Ramos; Marcelo Rollnic; Ramiro J. J. Neves (Theoretical and Applied Climatology, 2024)
Precipitation plays a vital role in various fields, including hydroclimatic modeling, climate change studies, agricultural optimization, and water resources management. Precipitation data can be obtained through observational measurements using the rain gauge approach or as Gridded precipitation products (GPP) derived from satellites or atmospheric models. GPPs provide optimized global estimates of climate data without spatial or temporal gaps, making them a valuable solution for areas with sparse or nonexistent rain gauges. However, it is essential to assess their reliability and limitations across different time scales and regions before usage. This study aims to evaluate the accuracy of two specific GPP datasets, ERA5 and MERRA-2, in comparison with two observational datasets, focusing on the Tocantins-Araguaia watershed and Pará river estuary in Brazil. The results show that both GPPs, ERA5 and MERRA-2, captured the overall precipitation regime for the analyzed period. However, discrepancies emerged, particularly at the daily and annual scales, with better agreement observed at monthly and climatology scales when compared to observational datasets. ERA5 demonstrated a higher number of acceptable stations compared to MERRA-2. Although both reanalysis products showed good agreement in climatological analysis, a more detailed evaluation revealed shortcomings in simulating precipitation during the dry season. While GPPs offer consistent time series with higher temporal and spatial resolutions, the observational precipitation data is deemed the most suitable input for hydrological-hydrodynamic modeling in the Tocantins-Araguaia watershed. Its widespread coverage, numerous rain gauges, and accurate representation of reality make it an ideal choice for hydrological modeling in the region.

Upscaling local domains in regional domains: An offline nudging approach - João Sobrinho; Hilda de Pablo; Lígia Pinto; Ramiro Neves (Environmental Modelling & Software, 2023)

Evaluation of diazepam adsorption in aqueous media using low-cost and natural zeolite: equilibrium and kinetics - Thaísa Frossard Coslop; Ramiro Picoli Nippes; Rosangela Bergamasco; Mara Heloisa Neves Olsen Scaliante (Environmental Science and Pollution Research, 2022)

Hydroxychloroquine Adsorption in Aqueous Medium Using Clinoptilolite Zeolite - Ramiro Picoli Nippes; Paula Derksen Macruz; Luiza Carla Augusto Molina; Mara Heloisa Neves Olsen Scaliante (Water, Air, & Soil Pollution, 2022)

Framework for Improving Land Boundary Conditions in Ocean Regional Products - Francisco Campuzano; Flávio Santos; Lucian Simionesei; Ana R. Oliveira; Estrella Olmedo; Antonio Turiel; Rodrigo Fernandes; David Brito; Marco Alba; Antonio Novellino; Ramiro Neves (Journal of Marine Science and Engineering, 2022)
The coupling of coastal or regional ocean models to hydrological models or observed data is currently an uncommon practice in operational oceanography. Though hydrological models are regarded as a powerful and useful tool for estimating the quantity and quality of freshwater running in a watershed, they fail to provide accurate results for river flow reaching the coastal area due to water-management activities occurring within the river catchment, activities such as human consumption, irrigation, storage, etc. For this reason, many coastal and regional ocean models continue to impose surface zero-salinity discharges as land boundary conditions for representing such a dynamic boundary. Moreover, river flows are based in climatologies, thus neglecting seasonal and interannual variability. To achieve those objectives, this study proposes an integrated methodology ranging from watershed models to validation in the coastal area and passing through methods and proxies for integrating the freshwater flows into regional ocean models. The main objective of this study is to explore the results obtained by using more sophisticated land boundary conditions based on the capacities of state-of-the-art hydrologic models combined with observation networks. In addition to the evaluation of the source of river-flow data, this work also explores the use of estuarine proxies based on simple modelling grids. The estuarine proxies enable the incorporation of the mixing processes that take place in estuaries into the land fluxes and obtain the plume momentum. The watershed, estuarine proxies, and ocean were modelled using the MOHID Water modelling system and evaluated in western Iberia waters. The modelling results served to illustrate the sea surface salinity extension of the Western Iberia Buoyant Plume (WIBP) during an extreme event in March 2018.

The Influence of the River Discharge on Residence Time, Exposure Time and Integrated Water Fractions for the Tagus Estuary (Portugal) - Hilda de Pablo; João Sobrinho; Daniel Garaboa-Paz; Caio Fonteles; Ramiro Neves; Miguel B. Gaspar (Frontiers in Marine Science, 2022)
Understanding how long water is retained in an estuary and how quickly it is completely flushed is essential to estimate an estuary’s health in areas with significant pollutant loadings. The present study analyses the effect of five different Tagus River discharge scenarios ranging from low to extreme on residence time (RT), exposure time (ET) and integrated water fractions inside pre-established Tagus estuary areas, to identify its most vulnerable areas to pollution. The 3D version of the MOHID hydrodynamic model coupled to a lagrangian tool was used. The increase of the river discharge generated high current velocities which, in turn, led to an increased rate of tracers leaving the estuary. As a consequence, RT and ET decreased from 59 to 3.5 days under a low and extreme river discharge scenario, respectively. Under a low river discharge, significant differences were observed between RT and ET in the areas located in the main body of the estuary and in the bays. As river discharge increased, RT and ET decreased in all areas of the estuary and those differences faded, with the greatest differences observed in the areas situated along the south margin. In general, results showed that with high river discharges the tracers released in the upper estuary are spread throughout the estuary, but mainly in downstream areas. However, when the river discharge reached exceptionally high values, local eddies were formed, leading to the retention of the tracers in the estuary’s south margin and inner bays. The results in this study allowed to identify the most vulnerable areas within the estuary as a function of the river discharge.

Coastal Ocean Observing and Modeling Systems in Brazil: Initiatives and Future Perspectives - Guilherme Franz; Carlos A. E. Garcia; Janini Pereira; Luiz Paulo de Freitas Assad; Marcelo Rollnic; Luis Hamilton P. Garbossa; Letícia Cotrim da Cunha; Carlos A. D. Lentini; Paulo Nobre; Alexander Turra; Janice R. Trotte-Duhá; Mauro Cirano; et al. (Frontiers in Marine Science, 2021)
Coastal ocean observing and modeling systems (coastal observatories), connected with regional and global ocean systems, improve the quality of information and forecasts for effective management of safe and sustainable maritime activities. The public availability of systematic and long-term information of the ocean is an engine for the Blue Economy, boosting economic growth, employment, and innovation. An overview of some Brazilian initiatives is presented in this paper, involving universities, private companies, federal and state agencies, covering institutions from south to north of Brazil. Although these initiatives focus mainly on ocean physics, integrated efforts can extend the scope to include biogeochemistry and marine biodiversity, helping to address interdisciplinary problems. Existing initiatives can be connected, and new ones fostered, to fill in the gaps of temporal and spatial coverage of ocean monitoring in the vast oceanic area under Brazilian jurisdiction (nationally referred to as the Blue Amazon, in reference to the similar richness of the Amazon Forest). The alignment among national and regional initiatives, as well as with international programs, can be promoted if coordinated by a national-level organization, maximizing the return of public investment and socioeconomic benefits. In light of international examples, possible future institutional arrangements are discussed, leveraging from existing national public policies and international cooperation that Brazil is taking part. The United Nations Decade of Ocean Science for Sustainable Development is a timely opportunity to encourage an institutional arrangement to support and articulate an integrated network of coastal observatories in Brazil.

How much leaf area do insects eat? A data set of insect herbivory sampled globally with a standardized protocol - Gisele M. Mendes; Fernando A. O. Silveira; Carolina Oliveira; Wesley Dáttilo; Roger Guevara; Betsabé Ruiz‐Guerra; Maria Gabriela Boaventura; Sershen; Syd Ramdhani; Shyam S. Phartyal; Sérvio P. Ribeiro; Victor Diniz Pinto; et al. (Ecology, 2021)
Herbivory is ubiquitous. Despite being a potential driver of plant distribution and performance, herbivory remains largely undocumented. Some early attempts have been made to review, globally, how much leaf area is removed through insect feeding. Kozlov et al., in one of the most comprehensive reviews regarding global patterns of herbivory, have compiled published studies regarding foliar removal and sampled data on global herbivory levels using a standardized protocol. However, in the review by Kozlov et al., only 15 sampling sites, comprising 33 plant species, were evaluated in tropical areas around the globe. In Brazil, which ranks first in terms of plant biodiversity, with a total of 46,097 species, almost half (43%) being endemic, a single data point was sampled, covering only two plant species. In an attempt to increase knowledge regarding herbivory in tropical plant species and to provide the raw data needed to test general hypotheses related to plant–herbivore interactions across large spatial scales, we proposed a joint, collaborative network to evaluate tropical herbivory. This network allowed us to update and expand the data on insect herbivory in tropical and temperate plant species. Our data set, collected with a standardized protocol, covers 45 sampling sites from nine countries and includes leaf herbivory measurements of 57,239 leaves from 209 species of vascular plants belonging to 65 families from tropical and temperate regions. They expand previous data sets by including a total of 32 sampling sites from tropical areas around the globe, comprising 152 species, 146 of them being sampled in Brazil. For temperate areas, it includes 13 sampling sites, comprising 59 species. Thus, when compared to the most recent comprehensive review of insect herbivory (Kozlov et al.), our data set has increased the base of available data for the tropical plants more than 460% (from 33 to 152 species) and the Brazilian sampling was increased 7,300% (from 2 to 146 species). Data on precise levels of herbivory are presented for more than 57,000 leaves worldwide. There are no copyright restrictions. Please cite this paper when using the current data in publications; the authors request to be informed how the data is used in the publications.

Atmospheric Influence Over the Residence Time in the Bahia Blanca Estuary, Argentina - Jorge O. Pierini; Francisco Javier Campuzano; Paulo C. Leitão; Eduardo A. Gómez; Ramiro J. Neves (Thalassas: An International Journal of Marine Sciences, 2019)

Modelling of sediment transport and morphological evolution under the combined action of waves and currents - Guilherme Franz; Matthias T. Delpey; David Brito; Lígia Pinto; Paulo Leitão; Ramiro Neves (Ocean Science, 2017)
Coastal defence structures are often constructed to prevent beach erosion. However, poorly designed structures may cause serious erosion problems in the downdrift direction. Morphological models are useful tools to predict such impacts and assess the efficiency of defence structures for different scenarios. Nevertheless, morphological modelling is still a topic under intense research effort. The processes simulated by a morphological model depend on model complexity. For instance, undertow currents are neglected in coastal area models (2DH), which is a limitation for simulating the evolution of beach profiles for long periods. Model limitations are generally overcome by predefining invariant equilibrium profiles that are allowed to shift offshore or onshore. A more flexible approach is described in this paper, which can be generalised to 3-D models. The present work is based on the coupling of the MOHID modelling system and the SWAN wave model. The impacts of different designs of detached breakwaters and groynes were simulated in a schematic beach configuration following a 2DH approach. The results of bathymetry evolution are in agreement with the patterns found in the literature for several existing structures. The model was also tested in a 3-D test case to simulate the formation of sandbars by undertow currents. The findings of this work confirmed the applicability of the MOHID modelling system to study sediment transport and morphological changes in coastal zones under the combined action of waves and currents. The same modelling methodology was applied to a coastal zone (Costa da Caparica) located at the mouth of a mesotidal estuary (Tagus Estuary, Portugal) to evaluate the hydrodynamics and sediment transport both in calm water conditions and during events of highly energetic waves. The MOHID code is available in the GitHub repository.

Coupling watersheds, estuaries and regional ocean through numerical modelling for Western Iberia: a novel methodology - Francisco Campuzano; David Brito; Manuela Juliano; Rodrigo Fernandes; Hilda de Pablo; Ramiro Neves (Ocean Dynamics, 2016)

Numerical Simulation of Soil Water Dynamics Under Stationary Sprinkler Irrigation With Mohid‐Land - Lucian Simionesei; Tiago B. Ramos; David Brito; Eduardo Jauch; Pedro C. Leitão; Carina Almeida; Ramiro Neves (Irrigation and Drainage, 2016)
Water distribution in sprinkler irrigation systems remains one of the most challenging problems in irrigation water management. Due to lack of water distribution uniformity, parts of a field may be over‐irrigated while others may be under‐irrigated, thus affecting root water and nutrient uptake and crop yield. The objective of this paper was to show the capabilities of the MOHID‐Land model in simulating soil water dynamics and maize growth under a stationary sprinkler irrigation system with low water distribution uniformity (56%). A 3D simulation domain (28 × 26 × 1 m) was defined to consider different water application rates at the soil surface and the variability of the soil hydraulic properties (two soil types). The model was able to take into account the effect of water distribution and soil variability on soil water content and fluxes, root water uptake reductions due to water stress, soil evaporation, leaf area index and total dry biomass. The resulting soil water balance revealed that irrigation inputs were lower (329 mm) than those theoretically defined to fulfil crop water requirements when the variable‐rate application of water was not considered (540 mm). Consequently, the range of variation of soil water stress in the simulation domain was relatively large (between 1 and 64%). MOHID‐Land has thus the potential of becoming an important tool for precision irrigation by focusing on site‐specific irrigation and crop management rather than the current field unit approach. Copyright © 2016 John Wiley & Sons, Ltd.

Influence of tide and waves on water renewal in Óbidos Lagoon, Portugal - Madalena S. Malhadas; Ramiro J. Neves; Paulo C. Leitão; Adélio Silva (Ocean Dynamics, 2010)

The autonomous Simpatico system for real-time continuous water-quality and current velocity monitoring: examples of application in three Portuguese estuaries - Erwan Garel; Susana Nunes; João Magalhães Neto; Rodrigo Fernandes; Ramiro Neves; João Carlos Marques; Óscar Ferreira (Geo-Marine Letters, 2009)

A methodology to estimate renewal time scales in estuaries: the Tagus Estuary case - Frank Braunschweig; Flvio Martins; Paulo Chambel; Ramiro Neves (Ocean Dynamics, 2003)

Biochemical characterization of embryogenic and non-embryogenic calluses of sugarcane - Nadina Neves; Magdalena Segura-Nieto; María A. Blanco; Margelys Sánchez; Alfredo González; Justo L. González; Ramiro Castillo (In Vitro Cellular & Developmental Biology - Plant, 2003)

3D-numerical modelling of cohesive suspended sediment in the Western Scheldt estuary (The Netherlands) - Leonor Cancino; Ramiro Neves (Aquatic Ecology, 1994)

Numerical modelling of suspended sediment transport in tidal estuaries: A comparison between the Tagus (Portugal) and the Scheldt (Belgium-the Netherlands) - Luis Ivens Portela; Ramiro Neves (Aquatic Ecology, 1994)